Information Search for Foreign Direct Investment Using Two-Stage Country Selection Procedures: A New Procedure - Ehrman, Chaim Meyer; Hamburg, Morris (Journal of International Business Studies, 1986)
This paper reports the development and testing of a normative model for determining how firms should select the countries to be used in the information search for foreign direct investment. After a subset of countries is selected in the first stage of the decision process, a final selection process chooses the country with the best score within the subset: A “percentile method of subset selection” for singling out clusters of countries for information search and for identifying the best of the subset is presented that performs better than maximum country rankings (“top means”) and maximum uncertainty (“top variance”) techniques of subset selection. As an illustration, the percentile selection method is applied empirically.